A discrete numerical model involving partial fluid-solid coupling to describe suffusion effects in soils. (March 2018) - Aboul Hosn, R.; Sibille, L.; Benahmed, N.; Chareyre, B.
Abstract: Suffusion is a particular case of internal erosion in soils. It is a particle-scale mechanism involving the selective erosion of fine particles within the matrix of coarse particles under the effect of water seepage. Modifications in the microstructure as a consequence of the loss of a fine fraction may affect both the hydraulic and the mechanical properties of the soil. Thus leading, in some cases, to drastic consequences. In this study, a methodology based on a discrete numerical model is introduced to investigate the initiation and development of suffusion as well as to analyze its effects on the soil mechanical properties. For that purpose, an original numerical extraction procedure was developed allowing us to mimic the suffusion process by taking into account both the microstructure of the granular packing and the hydraulic loading in the suffusion development. Such a procedure is based on a one-way fluid-solid coupling where the interstitial flow is solved with a finite volume approach defined at the pore scale. Numerical soil samples subjected to different hydraulic gradients show that depending on the amount and the role of eroded particles in the granular assembly two distinct responses can be expected. The eroded medium either shows negligible deformations during erosion but then collapses suddenly once sheared or it deforms significantly during erosion and shows more reduced strength once subjected to shear forces. A non-linear relation between the eroded mass and the mechanical properties of the soil was found.